Mechanical and morphological properties of polypropylene / natural rubber blending with additives / Anuar bin Jusoh - Jusoh, Anuar (2005)
One of the most successful methods developed for modifying and enhancing polymer properties is by polymer blending. This thesis project will focus on study of mechanical and morphology properties polypropylene (PP)/natural rubber (NR) with additive to produce a new properties polypropylene. Blends of polypropylene (PP) with elastomer are developed with the objective to overcome the inherent brittleness of PP at low temperatures and to enhance the impact strength at room temperature. The polymer blends of PP/NR will form so-called a thermoplastic natural rubber (TPNR). Thermoplastic natural rubber (TPNR) ts incompatible polymer pair and the technological compatibilization was sought by the addition dicumyl peroxide (DCP) and co-agent is N, N phenylenebismaleimide (HVA-2). In this study, the DCP and HVA-2 was also shown to be an effective compatibilizer by reducing the interfacial tension and improving adhesion between immiscible polymers thus increasing the compatibility of the blend. The blends were prepared in an extruder laboratory with various compositions. After mixing and palletizing, the samples were then injection molded and test for mechanical properties. This was including testing on tensile test, flexural test, and impact test. Differential Scanning Calorimeter (DSC) and Scanning Electron Microscope (SEM) also used to evaluate the morphology of the PP/NR blends. From the results in this thesis, an increase in impact strength and elongation at break but a decrease of tensile strength, yield strength, break strength and flexural modulus were observed with increasing natural rubber (NR).